Siblings with severe pyruvate kinase deficiency and a complex genotype. Issue 9 (29th June 2016) - Christensen, Robert D.; Yaish, Hassan M.; Nussenzveig, Roberto H.; Agarwal, Archana M.
Abstract : Siblings presented as neonates with severe jaundice and transfusion‐dependent hemolytic anemia. Next‐generation sequencing revealed both to have three heterozygous mutations in the gene encoding erythrocyte pyruv ate kinase ( PKLR ), plus a heterozygous splice mutation in the beta‐spectrin gene ( SPTB ). In addition, both have a different 5th mutation in a gene encoding other erythrocyte membrane proteins. The asymptomatic parents and all three asymptomatic siblings have different sets of these mutations. © 2016 Wiley Periodicals, Inc.